Study of the effects of methylphenidate (Ritalin) in an animal model for attention-deficit hyperactivity disorder : the spontaneously hypertensive rat - Lelaka, Gosiamemang Lesego Sadi (Department of Medicine, 2014)
Includes bibliographical references (leaves 83-99).